Factors affecting students enrollment at Selangor International University College (KUIS) / Ammar Asbi - Asbi, Ammar (Faculty of Business Management, 2006)
This research was conducted for the purposed of "Factors Affecting Students Enrollment at Selangor International University College (KUIS)". The main objective of this research was to identify the factors that affecting at KUIS which can also increase the number of students enrolment. For the purpose of study, descriptive research design had been adopted. The respondent of this study was potential school leavers which were 50 respondents of SPM/STPM holders from Sekolah Kebangsaan Menengah Seri Serdang and Sekolah Menengah Seri Indah. 50 questionnaires had been distributed to those SPM/STPM holders. The researcher had used stratified convenience sampling as the sampling technique. In this study, descriptive statistics had been used to interpret the data such as reliability test, tabulation analysis and cross tabulation and chi square test. From the findings, the communication and image factor was the most effective factor in KUIS. The fees factor was the least effective factor at KUIS. The conclusion of this study was the outcome from the survey analysis and findings. Through the research, it shows that KUIS must improve on fees factor which is the most least effective factor.